Religion and Peace Building - Bushra, Dr.; Akber, Ms. Tahira; Yasmeen, Ms. (Al Khadim Research Journal of Islamic Culture and Civilization, 2025)
This study examines the positive role of religion in peace building, exploring how religious beliefs, practices, and leaders can contribute to healing divided communities and fostering lasting peace. Despite the historical and ongoing association of religion with conflict, this research highlights the significant potential of religious teachings and leaders to promote reconciliation and unity. The study's literature review synthesizes insights from various academic disciplines, including politics, international relations, and peace and conflict studies, to provide a comprehensive understanding of how religion can be leveraged for peace building efforts. The objectives of the study are threefold: to explore how religious teachings encourage peace and forgiveness, to examine real-world examples where religious leaders and communities have successfully fostered unity, and to identify the challenges that these peace building efforts face. A qualitative research approach is employed, involving a review of existing literature on religious peace building practices, case studies of successful interfaith initiatives, and interviews with religious leaders and peace building practitioners. Data is drawn from diverse geographical regions, including Africa, Asia, and the Middle East, offering a broad perspective on religious contributions to peace building. The findings indicate that when religious teachings are embraced with openness and compassion, they can serve as powerful tools for healing divisions and bringing people together. The study presents numerous examples from different regions where religious leaders have played critical roles in mediating disputes and fostering dialogue. However, it also acknowledges the challenges inherent in religious peace building, particularly when religious identity is used to justify exclusion or marginalization. In conclusion, the research underscores the potential of religion to be a significant force for peace, provided its positive aspects are nurtured. Promoting interfaith dialogue and actively involving religious leaders in peace efforts are essential strategies for harnessing this potential. By focusing on the peace-promoting capabilities of religion, more effective approaches to conflict resolution can be developed, contributing to a more peaceful world.